Leksikon Alam dalam Lagu Daerah Tanduk Majheng sebagai Pembentukan Identitas Budaya Masyarakat Madura: Analisis Ekolinguistik - Bahruddin Bahruddin; Irfan Irwiadi; Imam Agus Basuki; Martutik Martutik (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
The form of nature lexicon in the Madurese folk song titled “Tanduk Majheng” reflects the cultural identity of its people. The song contains thoughts and noble values that have been passed down from generation to generation. The use of nature lexicon in the song is not only for entertainment, but also a medium for Madurese people to convey their ideas, advice, and outlook on life. Therefore, this study aims to describe and explain the form of nature lexicon used in Madurese folk song titled “Tanduk Majheng”, as well as the relationship contained in the song “Tanduk Majheng” as the cultural identity of Madurese people. This research is a qualitative descriptive research. The data source used is a Madurese folk song entitled “Tanduk Majheng”, while the data is taken from the form of lexicon related to nature as a form of ecolinguistic study. The results of the study found three forms of nature lexicon are 1) majhengan (fish finder), 2) abental ombek (cushioned waves), 3) asapok angen (covered with wind). The cultural identity of Madurese people in the song Tanduk Majheng lies in the form of nature lexicon which mentions that the habits of people who live on the coast with livelihoods at sea. The natural lexicon contains values such as hard work, independence, and a deep understanding of the marine environment.